2022
DOI: 10.1177/09713557211069283
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differentials in Entrepreneurship: Insights from a Multi-method Study

Abstract: Gender inequality is an obstacle to inclusive growth, and literature reveals shortcomings in the basic entrepreneurial assumption of equal access to resources, support and economic opportunities for women. International bodies have emphasised the need to examine gender differentials at various levels like, country, organisational and individual levels. Our study is a novel attempt in this direction and aims to build a comprehensive understanding of gender differentials in entrepreneurship using multi-method re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…However, as replied by the respondents, very few have undergone business-related training even after venturing let alone in advance. This point is corroborated by a recent study by Yadav et al (2022) where it was found only 9% reported any formal training or course on entrepreneurship. As suggested by Hurst et al (2008), it may be difficult to summarize an absolute profile of a successful entrepreneur.…”
Section: Discussionsupporting
confidence: 78%
“…However, as replied by the respondents, very few have undergone business-related training even after venturing let alone in advance. This point is corroborated by a recent study by Yadav et al (2022) where it was found only 9% reported any formal training or course on entrepreneurship. As suggested by Hurst et al (2008), it may be difficult to summarize an absolute profile of a successful entrepreneur.…”
Section: Discussionsupporting
confidence: 78%
“…However, care needs to be exercised as the actions may not be generalizable as socio-cultural, economic and policy situations vary immensely across nations. One example could be the inadequate capturing of household or social characteristics leading to gender disaggregation of data (Yadav et al , 2022) or the unfortunate fact that the show is managed by male members where women are only silent partners with business registrations in their name (Rajan and Panicker, 2020). Policymakers need to ensure that right policies reach and benefit rightful candidates thus encouraging the future generation of WEs.…”
Section: Implications For Women Entrepreneurship and Competency Devel...mentioning
confidence: 99%
“…Recent research publications shed light on the gender equality lacuna and call for sex-disaggregated studies addressing the macro and micro factors affecting women entrepreneurship in developing nations (Yadav et al, 2022). Despite the fact that institutionalized gender bias in emerging economies tends to limit entrepreneurial activity, it is found that women led enterprises can be a valuable source of innovation.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Necessity and opportunity entrepreneurs were found to differ in their socioeconomic attributes, the nature of the opportunities taken up, and their corresponding determinants of success. Especially, when studying women's entrepreneurship in emerging economies, behavioral economists usually place greater emphasis on the context in which decisions are made (Yadav et al, 2022). Specific factors like the national economy, available employment opportunities or lack thereof, social and cultural pressures may influence the motives of the female entrepreneur.…”
Section: Introductionmentioning
confidence: 99%